Quantification in bone SPECT/CT - Jovana Zivanovic; Jules Zhang-Yin (Frontiers in Nuclear Medicine, 2026)
Background Quantitative bone SPECT/CT enables objective assessment of skeletal radiotracer uptake using standardised uptake values (SUVs) and related parameters. Advances in reconstruction, correction methods, calibration and detector technology have improved measurement reliability and expanded interest in oncological and benign skeletal applications. This review evaluates current clinical applications, technical limitations and future directions of quantitative bone SPECT/CT. Methods PubMed was searched for English-language full-text human studies published from January 2015 to March 2025 using a reproducible Boolean strategy focused on quantitative or semi-quantitative bone SPECT/CT. Screening followed PRISMA 2020 principles. Thirteen primary studies were included in the qualitative synthesis; reviews, case reports, guidelines, position papers and other supporting publications were used only for narrative context. Results Quantitative bone SPECT/CT showed potential value for differentiating benign from malignant bone lesions, comparison with 18F-NaF PET/CT, longitudinal response assessment and prognostic evaluation before bone-targeted radionuclide therapy. Potential applications were also identified in condylar hyperplasia, fibrous dysplasia, vertebral compression fractures and degenerative joint disease. However, most studies were retrospective, single-centre and technically heterogeneous. Reported SUV thresholds were influenced by tumour type, lesion phenotype, uptake time, acquisition/reconstruction parameters, calibration, segmentation and recovery-coefficient methods, limiting transferability. Conclusions Quantitative bone SPECT/CT is a promising technique for objective assessment of bone metabolism, but current evidence supports cautious use as an adjunct to morphology and clinical context. Prospective multicentre studies with harmonised protocols, risk-of-bias control and patient-relevant endpoints are required. Artificial intelligence, radiomics, advanced detectors and theranostics should currently be considered research opportunities rather than established applications.